Effect of Black Garlic Extract in Feminine Liquid Soap as Antibacterial (Escherichia coli): Effect of Black Garlic Extract in Feminine Liquid Soap as Antibacterial (Escherichia coli) - Herliawati, Putu Arik; Wintariani, Ni Putu; Olivia, Brigita; Hildayanti, Rezha Alivia; Pratiwi, Nanda Agnesia Jati (Baiman Bauntung Batuah Center, 2023)
One of the causes of infection is pathological vaginal discharge caused by Escherichia coli. Handling of this infectious disease is still limited to giving antibiotics. So, an alternative therapy is needed using herbs. Black garlic is a fermented product that has stronger antibacterial properties. Based on this, it is necessary to test the potential of liquid soap with black garlic extract as antibacterial as scientific evidence. Research Objectives: To analyze the effect of black garlic extract on women's liquid soap on the growth of Escherichia coli. This research is quantitative research with an experimental research design. In this study, the intervention given was giving black garlic extract in feminism hygiene liquid soap preparations with various doses for bacteria Escherichia coli with disc diffusion technique. Black garlic extract was tested for phytochemicals to determine the content of active compounds. The results showed that black garlic extract in feminine hygiene liquid soap inhibited the growth of Escherichia coli bacteria; at a concentration of 40%, black garlic had the highest antibacterial activity with an average inhibition zone of 12.7mm. Therefore, it is proven that black garlic extract is effective as an antibacterial Escherichia coli in the formulation of feminine hygiene liquid soap.